Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1063/1.4972831
|View full text |Cite
|
Sign up to set email alerts
|

Very high thermoelectric figure of merit found in hybrid transition-metal-dichalcogenides

Abstract: The search for thermoelectrics with higher figures of merit (ZT) will never stop due to the demand of heat harvesting. Single layer transition metal dichalcogenides (TMD), namely MX 2 (where M is a transition metal and X is a chalcogen) that have electronic band gaps are among the new materials that have been the focus of such research. Here, we investigate thermoelectric transport properties of hybrid armchair-edged TMDs nanoribbons, by using the nonequilibrium Green's function technique combined with the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Although (ZT ) max shows a significant value when µ is far away from the LBE, its P F becomes vanishingly small. When compared with the band structures of TMDC and TMO materials calculated by the first-principle method, [19][20][21][22][23] we estimate Γ 0 to be between 5 meV and 15 meV . In this work, we adopte Γ 0 = 10 meV .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although (ZT ) max shows a significant value when µ is far away from the LBE, its P F becomes vanishingly small. When compared with the band structures of TMDC and TMO materials calculated by the first-principle method, [19][20][21][22][23] we estimate Γ 0 to be between 5 meV and 15 meV . In this work, we adopte Γ 0 = 10 meV .…”
Section: Resultsmentioning
confidence: 97%
“…In addition, the thermal conductivity of ITDMs is much smaller than that of their corresponding bulk materials [16][17][18]. Although the thermoelectric properties of ITDMs have been theoretically studied using the first-principle method [19][20][21][22][23], the contact and size effects on the electron transport of their heterostruc-tures are still unclear [24]. Because the unusual transport and optical properties of ITDMs originate mainly from the triangular (hexagonal) lattices (TLs) [25][26][27][28], their potential application to micro power generators and refrigerators calls for an investigation of the thermoelectric properties of finite 2D TLs coupled to electrodes as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Different kinds of nanoribbon structures have been studied for thermoelectric properties, including graphene nanoribbons (GNRs) of various shapes, [118 sp3-bonded graphane nanoribbons, [136] silicene and germanene nanoribbons, [137]- [139] TMDC nanoribbons, [140 [142] phosphorene nanoribbons [143], and hybrid superlattice nanoribbons. [144 [150], [137] Table 1 lists the reported ZT values of nanoribbons in the existing theoretical studies, which range from 0.1 to ~6 at RT.…”
Section: Nanoribbonsmentioning
confidence: 99%
“…[128], [129] In the superlattice nanoribbons consisting of hybrid 2D crystals ( Fig. 3 (b),(c), and(f), [144][150] ), the mechanisms of thermal conductivity reduction include the phonon-interface scattering and interference effects.…”
Section: Nanoribbonsmentioning
confidence: 99%
“…Layer mixing has shown to both improve power factor of 2D TMD-based thermoelectric devices and reduce the thermal conductance of the device [ 99 ]. Ouyang et al [ 100 ] showed via first principles calculations that hybrid interfaces drastically reduced thermal efficiency in armchair nanoribbons, resulting in extremely high ZT. Through their calculations, they found a MoS 2 /MoSe 2 armchair structure with an optimized ZT value of 7.4, higher than any other thermoelectric material previously calculated or fabricated.…”
Section: Tmd-based Thermocouple/thermoelectric Devicesmentioning
confidence: 99%